AKUNTABILITAS PT. KERETA API INDONESIA (KAI) DIVISI REGIONAL I SUMATERA UTARA DALAM PEMANFAATAN ASET - Viona Audelia Siregar; Dara Aisyah (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Asset management is a strategic aspect in supporting the performance and sustainability of state-owned enterprises, including PT Kereta Api Indonesia (Persero). PT KAI Regional Division I North Sumatra manages various assets, especially land and buildings, which have high economic and strategic value. However, in practice there are still several problems such as suboptimal asset utilization, limited asset management information systems, and land disputes due to leasing to third parties without accountable procedures. This study aims to analyze the accountability of PT KAI Regional Division I North Sumatra in asset utilization based on good governance principles. The research uses a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. The results show that PT KAI Regional Division I North Sumatra has implemented accountability principles such as compliance with regulations, transparency in reporting, and efficiency and effectiveness in asset utilization. However, improvements are still needed in optimizing asset management systems and strengthening supervision to prevent misuse of assets.